Non-oxidative hair dye products on the European market: What do they contain? - Hedberg, Yolanda S.; Uter, Wolfgang; Banerjee, Piu; Lind, Marie-Louise; Steengaard, Sanne Skovvang; Teo, Ying; Liden, Carola (Contact Dermatitis, 2018)
BACKGROUND: Hair dyeing is very common and may cause allergic contact dermatitis. Oxidative (often termed permanent or semi-permanent) hair dye products have constituted the focus of market surveys and toxicological risk assessments, while non-oxidative (semi-permanent, temporary or direct) products have not been assessed. OBJECTIVES: To identify the hair dye substances presently used in non-oxidative hair dye products in Europe. METHODS: Ingredient label data on eligible products in 5 European countries were collected, and 289 different non-oxidative hair dye products were included in this study. RESULTS: Up to 9 hair dye substances were present in each product. Sixty-eight individual hair dye substances were identified on the 289 product labels, and their occurrence ranged from 0.3% to 34%. There were differences concerning substances used and their number per product between products of different consistency and colour. CONCLUSIONS: The hair dye substances in non-oxidative hair dye products are different from those in oxidative hair dye products, and are currently not covered by patch test series. The toxicological and skin-sensitizing profile of the substances in non-oxidative hair dye products, as well as their concentrations, should be further investigated.
EVALuna2:35658